Critical Analysis of Obstacles and Opportunities in the Implementation of Peaceful Value-Based Higher Education Management - David, Muhammad; nuriyanti, Nuriyanti; Romadhoni, Dita; sultan, Sultan (LPPM Universitas Labuhanbatu, 2024)
ABSTRACTUniversities, as institutions of higher education, play an important role in shaping society and producing future leaders. One of the increasingly popular approaches to higher education management is peaceful values-based higher education management. The purpose of this study is to thoroughly analyze various articles, literature, and research reports related to the application of this approach. The results show that however, the research also points out many important opportunities, such as building an inclusive learning environment, building more moral leaders, and improving the public perception of the college. In addition, the research shows how important the integration of peaceful values in the higher education curriculum and cross-sectoral cooperation are. This research provides important information for higher education leaders, educational practitioners, and policy makers to make useful plans to face challenges and capitalize on opportunities to implement peaceful values-based higher education management, which can have a positive impact on society and the nation as a whole. Keyword: Challenges, Opportunities, Higher Education Management, Peaceful Values